Atypical hemolytic uremic syndrome: Korean pediatric series. Issue 3 (7th February 2015) - Lee, Jiwon M.; Park, Young Seo; Lee, Joo Hoon; Park, Se Jin; Shin, Jae Il; Park, Yong‐Hoon; Yoo, Kee Hwan; Cho, Min Hyun; Kim, Su‐Young; Kim, Seong Heon; Namgoong, Mee Kyung; Lee, Seung Joo; et al.
Abstract Background Atypical hemolytic uremic syndrome (aHUS) is a rare disease with a genetic predisposition. Few studies have evaluated the disease in the Asian population. We studied a Korean pediatric cohort to delineate the clinical characteristics and genotypes. Methods A multicenter cohort of 51 Korean children with aHUS was screened for mutations using targeted exome sequencing covering 46 complement related genes. Anti‐complement‐factor‐H autoantibody (anti‐CFH) titers were measured. Multiplex ligation‐dependent probe amplification assay was performed to detect deletions in the complement factor‐H related protein genes (CFHR) in the patients as well as in 100 healthy Korean controls. We grouped the patients according to etiology and compared the clinical features using Mann–Whitney U‐test and chi‐squared test. Results Fifteen patients (group A, 29.7%) had anti‐CFH, and mutations were detected in 11 (group B, 21.6%), including one with combined mutations. The remaining 25 (group C, 49.0%) were negative for both. The prevalence of anti‐CFH was higher than the worldwide level. Group A had a higher onset age than group B, although the difference was not significant. Group B had the worst renal outcome. Gene frequencies of homozygous CFHR1 deletion were 73.3%, 2.7% and 1% in group A, group B + C and the control, respectively. Conclusions The incidence of anti‐CFH in the present Korean aHUS cohort was high. Clinical outcomes largely conformed to the previous reports. Although the sample size was limited, this cohort provides a reassessment of clinicogenetic features of aHUS in Korean children.